(Re)Politicized and (Over)Sexualized―Wild(e) Treatments on Twenty-First-Century Viennese Stages - Mayer, Sandra (FOCUS: Papers in English Literary and Cultural Studies, 2012)
With Oscar Wilde’s reinvention as “Our Contemporary” and conveniently adaptable icon of postmodern culture in the last two decades, the author’s popular society comedies have evolved into an inexhaustible mine of multiple signification, inviting a broad range of interpretive disambiguation strategies. Inevitably, the diverse textual and dramaturgical schemes of adapting the plays for the twenty-first-century theatre market chiefly rely on what John Stokes has diagnosed as a “quality endemic to the plays: an interplay between performance, audience, and outside world”. Thereby engaging their biographical dimension in a “tangled web” of politics, popular culture, and postmodern aesthetics, contemporary Viennese theatrical readings of Wilde ultimately may be regarded as both reflecting and securing the playwright’s canonical survival.